A simulation analysis of economic and environmental factors in the design of an electric vehicle battery reverse supply chain - Vallejos, Melissa; Greasley, Andrew; Matopoulos, Aristides (SciTePress - Science and Technology Publications, 2024)
This article presents a study of a discrete-event simulation model of a UK reverse supply chain (RSC) for electric vehicle batteries. The purpose of the study is to use the model to run a set of simulated scenarios to explore how different operational strategies affect the RSC design configuration. The performance of the RSC can be measured in terms of its economic impact (such as the value of material recovered and production savings) and environmental impact (such as batteries recovered, remanufactured and repurposed, kg of materials recovered and CO2 emissions reduction). A key outcome of the study is that supply chain participants found that although they were aware of individual processes within the RSC the insights of the model covering the whole RSC and the metrics generated would enable them to make better informed RSC design decisions.